Energy Economics Concepts, Issues, Markets and Governance - Bhattacharyya, Subhes C. (Springer London, 2011)
Since its modest beginning in the 1970s, the academic and research focus on energy has grown substantially and energy has established itself as an independent, interdisciplinary subject area. It attracts attention from people in a range of different fields including engineers, scientists, geologists, environmentalists, bankers, investors, policy makers and politicians. Energy Economics introduces the basic concepts of energy economics and explains how simple economic tools can be used to analyse contemporary energy issues. Energy Economics is organised into six parts that give the reader a thorough grounding in various key aspects of the subject: basic demand-related concepts and ideas used in energy economics; supply-side economics; energy markets, with specific emphasis on oil, gas and coal; the application of simple economic principles in analysing contemporary energy issues; environmental aspects of energy use; and regulatory and governance issues. Energy Economics is an easily accessible reference book for students of energy economics at the postgraduate level, as well as for a wider interdisciplinary audience. It provides readers with the skills required to understand and analyse complex energy issues from an economic perspective.